2013
DOI: 10.1177/1941738113481428
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Nature, and Pattern of Injuries to Referees in a Premier Football (Soccer) League

Abstract: Background:Despite the crucial role of referees in a soccer match, few researchers have targeted the injury profile of referees in their studies. Understanding the incidence, nature, and pattern of injuries could provide important information for educational and preventative efforts at the international level.Hypothesis:The incidence rate and patterns of acute injuries to official referees of the Iranian Premier Football League during the 2009-2010 season are similar to those reported among referees in short-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
(25 reference statements)
2
19
0
2
Order By: Relevance
“…4,5,[10][11][12] The incidences of pain complaints, in matches and training, were higher than other studies, due to the characteristics of their definition. Wilson et al 5 and Kordi et al 11 presented lower rates than this study. Bizzini et al 10 also presented lower rates.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…4,5,[10][11][12] The incidences of pain complaints, in matches and training, were higher than other studies, due to the characteristics of their definition. Wilson et al 5 and Kordi et al 11 presented lower rates than this study. Bizzini et al 10 also presented lower rates.…”
Section: Discussionmentioning
confidence: 69%
“…The severity of the time-loss injuries classified as mild, which took from 1 to 7 days of interruption, prevailed both in matches (51.2%) and in training sessions (56%), which is similar to Wilson et al 5 , in which mild injuries prevailed. However, Kordi et al 11 found that most of the injuries were moderate with interruptions of 8 to 28 days. Bizzini et al 10 mentioned that no referee had any time loss in the 2006 World Cup; they only modified their activities in training.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the reports that were found were diverse. : from kickboxing and TBI in Qatar and Turkey (Slimani et al, 2017;Tanrivedi et al, 2007), fishing and aerial sport injuries as well as boxing related injuries in Turkey (Aydin, 2019;Cevik et al, 2016;Tanrivedi et al, 2008), to contact football and other team balls in Iran and Israel (Kordi et al, 2013;Kaplan et al, 2013), to new data on E-Biking with resulting serious injuries in Israel and Iran (Gross et al, 2018;Vahdati et al, 2016), rollover crashes as well as injuries related to Taekwondo and Karate in Iran (Anarkooli et al, 2017;Ziaee et al, 2010;Halabchi et al, 2007) and lastly camel jockeying injury in United Arab Emirates (UAE) (Abu-Zidan et al, 2012). Many countries focused on extremity injuries and were keen on detailing those injuries specifically; while data regarding head injury on the other hand was relatively sparse.…”
Section: Resultsmentioning
confidence: 99%